SISTEM PENDIDIKAN INKLUSI DAN INTERVENSI UMUM TERHADAP ANAK BERKEBUTUHAN KHUSUS - Angelina Cindya Bella; Arbidin Bayhaqi; Irene Meilika Putri; Esra Mariska Sianturi; Destin Natali; Adriansyah Pratama; Fitri Mayuta; Romiaty Romiaty (IKIP Siliwangi, 2026)
Education is a fundamental right of every citizen, including children with special needs, who require educational services tailored to their individual characteristics and needs. However, the implementation of inclusive education in Indonesia still faces various challenges, such as limited teacher understanding, inadequate facilities, and the lack of optimal integration between the education system and interventions provided. This study aims to analyze the education system for children with special needs and to examine general intervention strategies that support their development. The method used is a literature review by analyzing relevant scientific sources. The findings indicate that the education system for children with special needs has evolved from segregation to integration and inclusive models, although its implementation remains suboptimal. Furthermore, appropriate, planned, and individualized interventions play a crucial role in optimizing children’s academic, social, and independence development. Therefore, collaboration among policymakers, educators, families, and communities is essential to improve the quality of educational services and interventions for children with special needs.